The Influence of Marketing Mix 4p on The Loyalty of K-Pop Music Concert Audiences in Jakarta - Dita Hernita; Dewi Djunaedi, Mira Kartika (International Journal of Economics (IJEC), 2025)
The popularity of K-Pop in Indonesia continues to rise, with Jakarta frequently hosting major concerts that attract thousands of spectators. The increasing demand for K-Pop concerts has created competition among promoters, who must compete to provide the best experience for audiences through effective marketing strategies. This study aims to measure the effect of the 4P marketing mix strategy (Product, Price, Venue, Promotion) on the loyalty of K-Pop concertgoers in Jakarta. The research method used is quantitative with primary data collection through an online questionnaire. The population is aimed at millennials or generation Z who have attended a K-Pop concert in the last 3 months and are domiciled in DKI Jakarta. The research sample consisted of 115 respondents selected using purposive sampling techniques. Structural Equating Modeling (SEM) was used to determine the hypothesis testing between variables with SmartPLS software. The conclusion of this study shows that the four 4P marketing mix variables significantly influence the loyalty of K-Pop concertgoers in Jakarta. These results are expected to provide practical insights for K-Pop concert promoters and organizers in formulating effective marketing strategies to increase audience loyalty